Knowledge management and acquisition for intelligent systems : 14th Pacific Rim Knowledge Acquisition Workshop, PKAW 2016, Phuket, Thailand, August 22-23, 2016. Proceedings /: 14th Pacific Rim Knowledge Acquisition Workshop, PKAW 2016, Phuket, Thailand, August 22-23, 2016. Proceedings. (2016) - Unknown
No abstract available